Multiphoton Intravital Microscopy of Mandibular Draining Lymph Nodes: A Mouse Model to Study Corneal Immune Responses - Lopez, Maria J.; Seyed-Razavi, Yashar; Yamaguchi, Takefumi; Ortiz, Gustavo; Sendra, Victor G.; Harris, Deshea L.; Jamali, Arsia; Hamrah, Pedram (Frontiers in Immunology, 2020)
Multi-photon intravital microscopy (MP-IVM) is a powerful tool to image cells in vivo. Its application in immunology research has opened new horizons, allowing intravital imaging of leukocytes at the single cell level. A transparent cornea is vital to retain vision. As an immune privileged site, a quick innate response to foreign antigens is crucial in clearing opportunistic bacterial and viral pathogens and minimizing collateral structural damage to the cornea. Further, dissecting the mechanisms and preventing the rejection process after corneal transplantation is imperative to retain sight. Therefore, understanding the underlying mechanisms behind corneal immunity, specifically the process of antigen presentation and adaptive immunity in the mandibular draining lymph nodes (dLNs) in vivo, is crucial. Attempts of intravital imaging of mandibular dLNs has yielded little success to date due to breathing artifacts and the location that is difficult to access. Herein, we present the first MP-IVM mouse model of the mandibular dLNs, utilizing transgenic mice in which CD11c+ cells are fluorescently labeled. Further, we demonstrate that CD11c-YFP+ are localized mainly in the parafollicular cortex (T cell zone) and subcapsular area, and are sparsely distributed in the follicular region (B cell zone) during the steady state mandibular dLNs. A significant increase in host CD11c-YFP+ cell density is noted at 14 and 21 days following allogeneic corneal transplantation, compared to steady state (p<0.05). Moreover, allogeneic corneal transplantation results in increased host-derived CD11c-YFP+ cell mean speed and displacement in mandibular dLNs, compared to steady state (p<0.001). The meandering index, an index for directionality, was significantly increased after allogeneic corneal transplantation at both 14 and 21 days, compared to steady state (p<0.001). Taken together, our study demonstrates the necessary methodology required for intravital multiphoton imaging of the mandibular dLNs, allowing visualization of spatiotemporal kinetics of immune cells in vivo, and provides a window into the corneal immune reflex arc. This technique will be a powerful tool to investigate the pathogenesis of ocular immune and inflammatory diseases.